Local Market Reaction to Brand Acquisitions: Evidence from the Craft Beer Industry - Guler, Ali Umut; Misra, Kanishka; Singh, Vishal (Marketing Science, 2024)
Fifteen percent drop in local demand observed after acquisitions of local breweries by large firms.